TINGKAT KETERGANTUNGAN PENGGUNA MEDIA SOSIAL DAN KECEMASAN SOSIAL - Soliha, Silvia Fardila (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2015)
AbstractThis study aims to examine the correlation and influence between social anxiety and dependence on social media among the undergraduate students in Semarang. Quantitative descriptive method was being used to explain the causal relationship of two variables by collecting data that has been distributed to 100 respondents randomly selected by using a multistage random sampling. Validity test was done by using Spearman's technique and reliability analysis by Cronbach alpha coefficient formula with the result of high reliability of the instrument status. The test of the effect was using a simple linear regression analysis. The results of the research show there are positive and significant relationship between the level of social anxiety and dependence on social media with a strong enough relationship, as much as 31,4%, despite having very little effect, in which the statistical test results show the value of R Square of 12.7% of variance level of dependence on social media can be explained by changes in social anxiety variables with P-value = 0.000 which are much more smaller than Î± = 0:05. While the 87.3% part explained by other factors outside this research.